ANALISIS KETERAMPILAN MENGAJAR GURU PADA MUATAN PELAJARAN MATEMATIKA SISWA KELAS IV SDN 024 SAMARINDA UTARA - Oktaviani, Siska; Sapitra, Isa (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2020)
This research is a qualitative research which aims to analyze the teaching skills of teachers in the Mathematics content of class IVC students at SDN 024 North Samarinda. This research was conducted in June 2020 at SDN 024 Samarinda Utara. The resource persons in this study were the principal, class IVC teachers and class IVC students. The research results were collected through interviews and documentation. The data analysis technique uses data reduction, data presentation, data collection, and conclusion. The validity of the data is in the form of triangulation of sources, the results of the study prove that the teaching skills of teachers in Mathematics subject matter have a strategy when learning Mathematics, namely skills to open learning, core activities, and activities to close learning. The activity opens the lesson to say greetings, pray, attendance, and convey learning objectives. The core activities of the teacher are explaining the material, conducting questions and answers to find out student understanding, providing practice questions, the final activity of the teacher and students making conclusions on the material being taught, giving time for students to express their opinions about the learning that has been followed, praying for the closing of learning activities.